SEVEN SUGGESTION APPROACHES FOR PREVENTION OF MENTAL HEALTH PROBLEM AMONG STUDENTS IN HIGHER EDUCATION - Normadiah Mahiddin; Noraini Mohamed; Nur Hazirah Hamdan; Ramlan Mustapha (Journal of Islamic, Social, Economics and Development, 2023)
Mental Health is a very critical and prominent aspect needing attention among students studying in higher institutions. It is important for them to be able to juggle between their studies and other things pertaining to their academic life. Failure to cope and handle ever-changing situations will have a significant impact on their future. Previous studies show various reasons contributed to the rising cases of mental health problems among students such as financial concerns, unemployment, familial and relational difficulties, inadequate coping mechanisms, and lack of social support. Thus, this paper proposed a set of seven approaches to ensure healthy mental health among students in higher education. The Nominal Group Technique (NGT) has been applied as a methodology in this study. The approaches suggested have been presented in front of a group of seven experts through face to face. As a result, the approaches have been accepted with seven approaches being suggested with the arrangement of priority levels guided by experts. It is anticipated that the adoption and execution of the seven recommended measures will have a positive impact on the mitigation of mental health issues among students enrolled in institutions of higher education. Further and detailed research on every activity that has the effect of reducing cases of mental health problems should be carried out until we are able to eliminate the mental problems among students of higher education institutions.